Effects of Intense Exercise and Fluoxetine on Alterations Caused by Single Prolonged Stress in Female Rats - Sakineh Shafia; Gohar Ghahramani; Moslem Mohammadi; Saeed Kargar-soleimanabad (Journal of Mazandaran University of Medical Sciences, 2023)
Background and purpose: Post-traumatic stress disorder (PTSD) is a psychotic disorder that occurs in people who have faced with various types of stressors. However, the efficacy of drug and psychotherapy methods, even in combination is still low. Therefore, complementary treatments are being researched. The relative improvement of PTSD has been observed with the use of Serotonin Selective Reuptake Inhibitors (SSRIs). The effect of exercise has also been determined in improving physical and mental health. But the appropriate exercise intensity is still in question. Therefore, the aim of this study was to investigate the effect of intense exercise, fluoxetine, and their combined treatment on behavioral, molecular, and cellular damages caused by a standard model of PTSD. Materials and methods: Single prolonged stress (SPS) was used as a model to induce PTSD. Exercise (1 hour, 15 m/min) was planned for five days per week and fluoxetine (10 mg/kg/day) dissolved in drinking water was administered for four weeks. After performing the anxiety test, the animals were killed under deep anesthesia and blood samples were collected to measure IGF-1 serum levels by ELISA method and prefrontal cortex was frozen to measure apoptotic factors by RT-PCR method. Results: SPS rats showed increased anxiety levels and decreased serum IGF-1 levels. Increased Bax and Caspase-3 mRNA expression, and decreased Bcl2 mRNA expression were found in the prefrontal cortex. Exercise, fluoxetine, and their combined intervention increased IGF-1, decreased the expression of pro-apoptotic factors, and increased the expression of anti-apoptotic factors. The results showed that the combined intervention of exercise and fluoxetine could reduce the anxiety caused by SPS. Conclusion: Considering that fluoxetine was more effective in comparison with high-intensity exercise, it is clear that in the groups that were affected by both interventions; fluoxetine played a more significant role.